1969
DOI: 10.3181/00379727-132-34134
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Lymph Production in the Rat

Abstract: Several reports have shown the apparent superiority of NaCl solution over water as a lymphagogue; most of these studies have been carried out in ad libitum drinking animals (1). We have studied the effect of triglycerides, starch, casein, hormones, and Na+/K+ ratio on lymph flow. These studies were made possible by the development of a modified Bollman's technique for the cannulation of the abdominal thoracic duct in the rat (2), which includes the infusion of solutions into the duodenum at a constant rate to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
1987
1987

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Studies concerning the effect of ingestion of various food stuffs on the formation of lymph have shown that lipids strongly increase lymph flow [1][2][3]. The increase in the lymph volume partially comes from luminal absorption, but we have recently shown that increased accumulation of intestinal lymph may also be due to increased plasma protein leakage from the intestinal circulation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies concerning the effect of ingestion of various food stuffs on the formation of lymph have shown that lipids strongly increase lymph flow [1][2][3]. The increase in the lymph volume partially comes from luminal absorption, but we have recently shown that increased accumulation of intestinal lymph may also be due to increased plasma protein leakage from the intestinal circulation [4].…”
Section: Introductionmentioning
confidence: 99%